Microfluidic-Based Formulation of Essential Oils-Loaded Chitosan Coated PLGA Particles Enhances Their Bioavailability and Nematocidal Activity - Mohamed A. Helal; Ahmed M. Abdel-Gawad; Omnia M. Kandil; Marwa M. E. Khalifa; Alison A. Morrison; David J. Bartley; Gareth W. V. Cave; Hany M. Elsheikha (MDPI AG, 2022)
In this study, poly (lactic-co-glycolic) acid (PLGA) particles were synthesized and coated with chitosan. Three essential oil (EO) components (eugenol, linalool, and geraniol) were entrapped inside these PLGA particles by using the continuous flow-focusing microfluidic method and a partially water-miscible solvent mixture (dichloromethane: acetone mixture (1:10)). Encapsulation of EO components in PLGA particles was confirmed by Fourier transform infrared spectroscopy, thermogravimetric analysis, and X-ray diffraction, with encapsulation efficiencies 95.14%, 79.68%, and 71.34% and loading capacities 8.88%, 8.38%, and 5.65% in particles entrapped with eugenol, linalool, and geraniol, respectively. The EO components' dissociation from the loaded particles exhibited an initial burst release in the first 8 h followed by a sustained release phase at significantly slower rates from the coated particles, extending beyond 5 days. The EO components encapsulated in chitosan coated particles up to 5 μg/mL were not cytotoxic to bovine gut cell line (FFKD-1-R) and had no adverse effect on cell growth and membrane integrity compared with free EO components or uncoated particles. Chitosan coated PLGA particles loaded with combined EO components (10 µg/mL) significantly inhibited the motility of the larval stage of Haemonchus contortus and Trichostrongylus axei by 76.9%, and completely inhibited the motility of adult worms (p < 0.05). This nematocidal effect was accompanied by considerable cuticular damage in the treated worms, reflecting a synergistic effect of the combined EO components and an additive effect of chitosan. These results show that encapsulation of EO components, with a potent anthelmintic activity, in chitosan coated PLGA particles improve the bioavailability and efficacy of EO components against ovine gastrointestinal nematodes.